2019
DOI: 10.1016/j.ijepes.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Affine arithmetic for efficient and reliable resolution of weather-based uncertainties in optimal power flow problems

Abstract: The massive diffusion of renewable power generators in existing power grids introduces large uncertainties in power system operation, hindering their hosting capacity, and introducing several critical issues in network management. To address these challenging issues, weather-based optimal power flow has been recognized as one of the most promising enabling methodology for increasing the system flexibility by exploiting the real power components loadability. Anyway, the deployment of this technique in a real op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The STR and DTR limits are implemented on all lines, which are assumed to be ACSR 'Fox' conductor type, [35]. Detailed network information can be obtained from [34].…”
Section: Generated Cross-correlated Wind Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The STR and DTR limits are implemented on all lines, which are assumed to be ACSR 'Fox' conductor type, [35]. Detailed network information can be obtained from [34].…”
Section: Generated Cross-correlated Wind Profilesmentioning
confidence: 99%
“…For a given wind speed profiles, power outputs of wind turbines (WTs) in WF can be estimated through many approaches [34]. Most common approach is the use of manufacturer power curve, which specifies the relationship between the input wind speed and WT output power.…”
Section: Wind Profiles Load Profiles and Their Uncertaintiesmentioning
confidence: 99%
“…In 2019, Guido Coletta et al [4], addressed a problem in weather-based method, which was identified as a major potential facilitating technique in order to increase the system suppleness using the components of real power loadability. Nevertheless, in real operation circumstances, the consumption of this method could be acutely cooperation because of the uncertainty data effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier, numerous researchers examined on several optimization algorithms that exhibit the different issues and how it obtain and resolved with assist for the solution of the OPF [4]. Generally, two kinds of algorithms are exploited namely traditional and intelligent algorithms in order to resolve the OPF problems.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some progress has already been made in treating multiple uncertainties in power system analysis. A kind of affine arithmetic (AA) method was developed to model uncertain renewable generations in optimal power flow (OPF) problem [22, 23], and a weather‐based OPF was subsequently proposed based on the AA method [24]. As for the case where the probability, possibility, and interval measures were considered simultaneously, Luo et al .…”
Section: Introductionmentioning
confidence: 99%